PENGARUH PEMBELAJARAN KOOPERATIF METODE TALKING STICK TERHADAP MOTIVASI BELAJAR SISWA PADA MATERI BESARAN DAN SATUAN KELAS VII SMP N 2 KEPENUHAN - -, JUMIATI (Jurnal Ilmiah Mahasiswa FKIP Prodi FISIKA, 2016)
This research aims to look at and determine the effect of cooperative learning talking stick method to motivate students in the material quantities and units of class VII SMP N 2 Kepenuhan.This research uses regression analysis. Based on the data analysis the researchers found that the talking stick method of teaching positive effect on students motivation. Based on calculations using the data obtained was found that correlation rhitung = 0.9915 while the value rtabel respectively by 0.413. Thus t is greater than rtabel (rhitung> rtabel), the significant level of 5%. It can be concluded that there are significant cooperative learning talking stick method to motivate students in the material quantities and units of class VII SMP N 2 Kepenuhan.